Pengangguran, Kemiskinan, Tingkat Pendidikan Dan Produk Domestik Regional Bruto - Romualdus Turu Putra Maro Djanggo; Candra Agus Wahyudhi (EKONOMI & SOSIAL, 2020)
The study aims to analyse whether the unemployment, poverty and education factors affect gross Regional domestic product (GDP) in Merauke Regency in 2010-2018. The data used in this study is secondary data. The method of collecting data using secondary data from the official data is issued by the Department of Statistics Central of Merauke District. For data processing is done using SPSS 21 program. The results of this study showed the variables of unemployment, poverty and education for the four districts studied; The slope district, Kurik District, Naukenjerai District and Sota district are simultaneously affecting the value of the gross Regional domestic product (GDP) of Merauke Regency. Result coefficient of determination (R²) 91.7% indicates that the variables of unemployment, poverty, and education have a significant influence on the improvement of the gross Regional domestic product (GDP). From the results of this research can also be concluded that the unemployment variables that affect the change in the value of gross Regional domestic product (GDP) in Merauke District lower education impact on the gross Regional domestic product value ( GDP) is because awareness of the importance of education in this district is still minimal especially in four districts that are carefully